2013
DOI: 10.1002/app.39774
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides‐decorated‐poly(N‐vinyl pyrrolidone) nanogels for gene delivery

Abstract: Pulsed electron-beam irradiation of a semi-dilute poly(N-vinyl pyrrolidone) (PVP) aqueous solution in the presence of\ud acrylic acid has led to a carboxyl functionalized nanogel system. Nanoparticles hydrodynamic size and surface charge density, in water\ud and as a function of pH, were investigated by dynamic light scattering and laser doppler velocimetry, respectively. Nanogels (NGs)\ud were proved not to be cytotoxic at the cellular level. Indeed, they rapidly bypass the cellular membrane to accumulate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…As a result, HA shielding of PEI/pDNA nanogels ensured an effectively internalization of nanogels into human mesenchymal stem cells (hMSCs) and HeLa cells via receptors located in the plasma membrane, recommending these nanocarriers as gene delivery vehicles to induce stem cell differentiation. Dispenza et al (2014) reported the formulation and characterization of biocompatible PVP-AA nanogels surface bioconjugated with a single strand oligonucleotide (ODN). The bioconjugated nanogels exhibited colloidal stability and an excellent ability/capacity to bypass cell membrane, accumulating in perinuclear area of the cytoplasm.…”
Section: Bioconjugated Nanogels As Versatile Nanocarriersmentioning
confidence: 99%
“…As a result, HA shielding of PEI/pDNA nanogels ensured an effectively internalization of nanogels into human mesenchymal stem cells (hMSCs) and HeLa cells via receptors located in the plasma membrane, recommending these nanocarriers as gene delivery vehicles to induce stem cell differentiation. Dispenza et al (2014) reported the formulation and characterization of biocompatible PVP-AA nanogels surface bioconjugated with a single strand oligonucleotide (ODN). The bioconjugated nanogels exhibited colloidal stability and an excellent ability/capacity to bypass cell membrane, accumulating in perinuclear area of the cytoplasm.…”
Section: Bioconjugated Nanogels As Versatile Nanocarriersmentioning
confidence: 99%
“…Since the first appearance of this family of nanoscale materials, their application as biocompatible carriers for a large plethora of biomedical and biotechnological applications has been explored [3][4][5]. In particular, these soft materials have gained growing interest for drug delivery because of their high loading capacity and stability [6][7][8][9][10], showing also potential use as pH and temperature sensors [11,12]. They are also employed as in vivo imaging tracers [13], in water treatment [14] and catalysis [15], as smart gating membranes for the fabrication of active photonic crystals and coatings, and for generating bioactive scaffolds in regenerative medicine [16].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies using a "non-functional" ODN have shown that the covalent bond to the nanogel does not prevent the ODN binding ability to the complementary sequence, probably due to the exibility of the particle and its link to the ODN. 27 This result was never demonstrated on a cellular model and provides motivation for the present investigation. Moreover, the ability of NG-AntimiR-31 to permeate cell membrane was investigated in the metastatic SW620 colon cancer cell line, which expresses high levels of miR-31.…”
Section: Introductionmentioning
confidence: 78%